The Influence of Big Five Personality and School Climate on Junior High School Students' Altruism Attitudes - Arisanti, Dewi; Dadeh, Tarmidi; Sutatminingsih, Raras (Devotion : Journal of Research and Community Service, 2024)
This research investigates the influence of Big Five Personality traits and school climate on altruistic attitudes among junior high school students in Medan. Altruism, defined as selfless kindness, is crucial during adolescence, a transitional period marked by various changes. While foreign cultures and individualistic mindsets may hinder altruistic attitudes, teaching altruism from an early age is essential. The study aims to examine the impact of Big Five Personality traits (openness, conscientiousness, extraversion, agreeableness and neuroticism) and school climate on altruistic attitudes. The research involves 728 students from three schools and utilizes scales for personality, school climate, and altruism. The results indicate that school climate significantly predicts altruism, contributing 32%, while Big Five Personality traits contribute 12%. Openness, agreeableness and neuroticism personality types, along with safety and academic dimensions of school climate, play a significant role. Although the joint influence is limited (13.2%), school climate emerges as a more dominant factor in shaping altruistic attitudes among junior high school students. The findings emphasize the importance of fostering a positive school climate to enhance altruistic behaviors.